2022
DOI: 10.3390/ma15031014
|View full text |Cite
|
Sign up to set email alerts
|

Nanometers-Thick Ferromagnetic Surface Produced by Laser Cutting of Diamond

Abstract: In this work, we demonstrate that cutting diamond crystals with a laser (532 nm wavelength, 0.5 mJ energy, 200 ns pulse duration at 15 kHz) produced a ≲20 nm thick surface layer with magnetic order at room temperature. We measured the magnetic moment of five natural and six CVD diamond crystals of different sizes, nitrogen contents and surface orientations with a SQUID magnetometer. A robust ferromagnetic response at 300 K was observed only for crystals that were cut with the laser along the (100) surface orie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Due to high processability, studies of the magnetic properties of laser-graphitized films are of special interest. The observation of a stable ferromagnetic response at a temperature of 300 K from a 20 nm thick surface layer formed in the cut region of diamond crystal by a laser (wavelength 532 nm, energy 0.5 mJ, pulse duration 200 ns at the frequency of 15 kHz) is reported [33]. In this case, the magnetic moment measured by the SQUID magnetometer was observed only for crystals that were cut by a laser along the (100) surface orientation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Due to high processability, studies of the magnetic properties of laser-graphitized films are of special interest. The observation of a stable ferromagnetic response at a temperature of 300 K from a 20 nm thick surface layer formed in the cut region of diamond crystal by a laser (wavelength 532 nm, energy 0.5 mJ, pulse duration 200 ns at the frequency of 15 kHz) is reported [33]. In this case, the magnetic moment measured by the SQUID magnetometer was observed only for crystals that were cut by a laser along the (100) surface orientation.…”
Section: Introductionmentioning
confidence: 93%
“…The ferromagnetic signal (coercive fields ≈ 8 mT) disappeared after chemical etching or after moderate temperature annealing. According to [33], the results indicate that laser processing of diamond can lead to the creation of ferromagnetic spots on its surface. This phenomenon can be of interest not only for memory devices but also for other rather subtle applications [36][37][38][39], such as using a localized magnetic spot near a nitrogen-carbon vacancy (NV-center) to influence its magneto-optical response, especially to increase its field sensitivity at certain applied field ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Setzer et al investigated magnetic properties of natural and CVD diamonds after laser-cut. 145 All of them exhibited ferromagnetism after laser-cut owing to surface graphite formation on diamond surfaces. The surface graphites formed on CVD diamond surfaces were <20 nm thick after laser-cut and reduced by 10% after laser polishing of the laser-cut surface.…”
Section: Paramagnetic and Ferromagnetic Propertiesmentioning
confidence: 99%
“…Fig.11Zero-field-cooled and field-cooled curves of the CVD samples (#1a: samples after the laser-cut and #1b: after laser-polishing of the laser-cut surface) as a function of temperature between 2 and 380 K at applied fields of 0.01, 0.05, and 1 T 145. …”
mentioning
confidence: 99%
“…The laser treatment of materials was also successfully used in [ 29 ], where annealing by laser-heated electrospinning was proven to be efficient in producing ultrafine fibers. Heat transfer was even proven to be successful in changing the magnetic state of thin films in [ 30 ], where it was shown that cutting diamond crystals with a laser (532 nm wavelength, 0.5 mJ energy, 200 ns pulse duration at 15 kHz) produced a 20 nm thick surface layer with a magnetic order at room temperature. Laser-induced temperature changes might be suitable for the in situ monitoring of the repair of defective sites in fused-silica optical components [ 31 ].…”
Section: Introductionmentioning
confidence: 99%